Tinjauan Atas Putusan Pengadilan Agama Cibinong Nomor 7584/Pdt.G/2021/PA.Cbn tentang Pembatalan Perkawinan Akibat Mahar yang Terutang Dihubungkan dengan Undang-Undang Perkawinan dan Hukum Islam - Hanna Maulida Fitria; Renny Supriyatni; Linda Rachmainy (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The annulment of a marriage has legal consequences, namely that the marriage is declared invalid (no legal force on the declared void marriage). The Cibinong Religious Court Decision No. 7584/Pdt.G/2021/PA.Cbn is an example of a ruling on marriage annulment due to the dowry not being provided by the male party. This writing aims to examine the legal considerations in the Cibinong Religious Court Decision No. 7584/Pdt.G/2021/PA.Cbn, which annulled the marriage due to the unpaid dowry, based on the Marriage Law and Islamic Law. The research method used is normative legal research with an analytical descriptive approach. The approach is based on secondary data through literature studies, including primary, secondary, and tertiary legal materials. The data analysis method employed is qualitative juridical analysis. Based on the findings, it can be concluded that the legal reasoning behind the decision to annul the marriage due to unpaid dowry in Cibinong Religious Court Decision No. 7584/Pdt.G/2021/PA.Cbn, which was based on Article 27(2) of the Marriage Law in conjunction with Article 72(2) of the Compilation of Islamic Law, was less accurate.